Fabrication and Properties for Thermal Neutron Detection of 6LiCl/Rb2CeCl5 Eutectic Scintillator - Rei Sasaki; Kei Kamada; Masao Yoshino; Kyoung Jin Kim; Rikito Murakami; Takahiko Horiai; Akihiro Yamaji; Shunsuke Kurosawa; Yuui Yokota; Hiroki Sato; Yuji Ohashi; Takashi Hanada; et al. (Crystals, 2024)
The 3He gas is commonly used for the detection of thermal neutrons. However, with the depletion of 3He gas, there is a need to develop new solid scintillators for thermal neutron detection. Solid scintillators containing 6Li, which have large neutron capture cross-sections and a large amount of energy released by transmutation reactions, are commonly used as alternative candidates. However, only single-crystal scintillators are currently used, and their 6Li concentration is limited by their chemical composition. In this study, we designed, grew, and evaluated a new eutectic scintillator, Rb2CeCl5/LiCl, which can improve the 6Li concentration compared with single-crystal scintillators. Rb2CeCl5, which was selected as the scintillator phase, has excellent scintillator properties (light yield: 36,000 photons/MeV, decay time: mostly 24 ns, slightly 153 ns), and is less deliquescent than other halide scintillators. The crystal grown using the vertical Bridgman method exhibited a eutectic phase composed of Rb2CeCl5 and LiCl. The eutectic crystals exhibited Ce3+ 5d-4f emissions, with a peak between 360 and 370 nm. The Rb2CeCl5 phase was identified as the luminescent phase via cathodoluminescence mapping, and 16,000 photons/neutron of the light yield and 56.1 ns of the decay time were observed. This study indicates that the Rb2CeCl5/LiCl eutectic scintillator is a promising candidate for use in thermal neutron detectors.